Sources of Corporate Financing and Economic Crisis in Korea: A Micro-evidence - Youngjae Lim (Korea Development Institute (KDI), 2001)
Using the firm-level data set, this paper attempts to examine the dynamic patterns in the allocation of credit across firms in recent Korea. Supposedly, in Korea, the economic crisis in 1997 had a significant impact on the pattern in the allocation of credit across firms. In particular, this paper aims to examine these dynamic patterns across large and small firms after the crisis. Corporate financing issues are intimately related to the cause of the Korean crisis. For instance, the chaebols' indebtedness to banks is viewed as having contributed much to the crisis. In this regard, since the outbreak of the financial crisis in 1997, the government has undertaken various reform measures to restructure the financial and corporate sectors. The new regulatory system is now underway to induce the financial institutions to change their imprudent lending practices, and the capital market began to force the chaebols to correct their incentive structure. Supposedly, these post-crisis developments in Korea have caused the chaebols and financial institutions to change their previously imprudent (borrowing and lending) practices. The paper suggests that large firms, to some extent, are leaving banks and going to the capital market for their financing after the crisis. The paper also suggests that profitable small firms are gaining easier access to credit by financial institutions after the crisis. There has been a shift in the allocation of bank credit from large firms to small firms. Is this shift due to lenders' choice or due to borrowers' changed incentives? The paper suggests that the improved lending practices of banks, at least partially, contributed to this shift of bank credit from large firms to small firms.
Keywords: 330